The Status of Inclusive Education in Baluchistan: A Qualitative Investigation - Samina Ashraf; Rukhsana Bashir; Ghulam Fatima (Journal of Business and Social Review in Emerging Economies, 2020)
The central purpose of this qualitative study was to investigate the existing condition of the inclusive schools working in the province of Baluchistan, Pakistan. Out of six divisions of Baluchistan, Quetta division was selected purposively. After conducting a survey, eight inclusive schools were taken as sample from the regular schools. An observation sheet containing the components of school ecology, instructional practices of teachers, curriculum adaptations, classroom management, infra structure of schools, and use of teaching aids in the classrooms was prepared. In eight schools, 48 observations (three observations in grade three and four each) were conducted. The results reflected that most of the children were at the mild level of disability and teachers were paying attention to special children but due to lack of training in deaf education and unavailability of assistive devices, the anticipated outcomes were not being obtained. The conclusions were drawn and recommendations to the Department of Education, Government of the Baluchistan were given for the improvement of inclusive set up.